Encephalitis in children - Thompson, C; Kneen, R; Riordan, A; Kelly, D; Pollard, A (2012)
Encephalitis is an uncommon but potentially devastating neurological syndrome with different aetiologies including direct central nervous system infection with different agents (most commonly viral) and those mediated by the immune system. Whilst there have been several recent publications and guidelines on the management of bacterial central nervous system infections in adults and children, viral infections have been relatively neglected. Guidelines have been published for adults with encephalitis (www.liv.ac.uk/braininfections) but none exist for children. For these reasons, we have reviewed the literature on encephalitis and have formulated a suggested management strategy for children with suspected, clinically diagnosed and proven encephalitis. We have excluded neonates, as encephalitis in this age group has different clinical features and is beyond the scope of this review.